Report on the Incidence of Longer-Term Program Engagement. (Policy Papers; Policy Paper ;, 2013)
Longer-term program engagement (LTPE) occurs when a member has spent at least seven of the past 10 years under Fund-supported financial arrangements. In response to the Executive Board's request for periodic updates on the incidence of LTPEs, this is the fourteenth such report and provides information through July 1, 2013.